2019
DOI: 10.3390/s19010119
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Properties of Oxidized Nanostructured Silicon Surface on Vaporized Molecules

Abstract: Porous silicon has been intensely studied for the past several decades and its applications were found in photovoltaics, biomedicine, and sensors. An important aspect for sensing devices is their long–term stability. One of the more prominent changes that occur with porous silicon as it is exposed to atmosphere is oxidation. In this work we study the influence of oxidation on the sensing properties of porous silicon. Porous silicon layers were prepared by electrochemical etching and oxidized in a tube furnace.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Thus, the higher sensitivity of the APTES@WO3-x sensors to ethanol may be influenced by the higher polarity of this analyte given its larger electronegative difference (ΔEN = 1.4 for ethanol) in the polar region compared to acetone (ΔEN = 1) and carbon monoxide (ΔEN = 1) [30]. The correlation of the sensitivity and the polarity of various reducing analytes has also been noticed in recent literature reports [31]. Similarly, the sensitivity to nitrogen dioxide could be connected with the polar nature of this analyte and the high sensitivity of tungsten oxide to electron acceptor (oxidizing) than electron donor (reducing) analytes [32].…”
Section: Gas Sensing Testsmentioning
confidence: 57%
“…Thus, the higher sensitivity of the APTES@WO3-x sensors to ethanol may be influenced by the higher polarity of this analyte given its larger electronegative difference (ΔEN = 1.4 for ethanol) in the polar region compared to acetone (ΔEN = 1) and carbon monoxide (ΔEN = 1) [30]. The correlation of the sensitivity and the polarity of various reducing analytes has also been noticed in recent literature reports [31]. Similarly, the sensitivity to nitrogen dioxide could be connected with the polar nature of this analyte and the high sensitivity of tungsten oxide to electron acceptor (oxidizing) than electron donor (reducing) analytes [32].…”
Section: Gas Sensing Testsmentioning
confidence: 57%
“…The experiment has shown that the oxidation of PSi is the most effective method for solving problems associated with the instability of PSi properties . It was found that even slightly oxidized PSi may be more stable and may contain fewer interface states affecting Fermi‐level pinning.…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 99%
“…Porous silicon (por-Si) is very promising as a matrix material for gas sensors due to its high surface to volume ratio and reactivity with the environment as well as its hierarchical porous texture with different pore sizes that can be tuned for certain goals and also due to facility of integration with silicon microchips [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that por-Si has a potential use in sensing of organic vapors and ammonia when covered with an oxide layer [22]. Graphene decorated por-Si showed enhanced sensing property to low-ppm H 2 at room temperature in comparison to that of pristine por-Si [23].…”
Section: Introductionmentioning
confidence: 99%